Somatosensory and auditory processing in opioid-exposed newborns with neonatal abstinence syndrome: a magnetoencephalographic approach. (22nd November 2015) - Kivistö, K.; Nevalainen, P.; Lauronen, L.; Tupola, S.; Pihko, E.; Kivitie-Kallio, S.
Abstract: Objective : Opioid exposure during pregnancy is a potential risk factor for the developing central nervous system of the fetus. We studied evoked responses in buprenorphine-exposed newborns who displayed neonatal abstinence syndrome (NAS) to elucidate the possible alterations in functioning of the somatosensory and auditory systems. Methods : We compared somatosensory (SEFs) and auditory evoked magnetic fields (AEFs), recorded with magnetoencephalography (MEG), of 11 prenatally buprenorphine-exposed newborns with those of 12 healthy newborns. Peak latencies, source strength and location of SEFs or AEFs were recorded. Results : AEFs were present in all buprenorphine-exposed newborns without significant differences from those of healthy newborns. In contrast, though no group level differences in SEFs existed, at individual level the response deviated from the typical neonatal morphology in four buprenorphine-exposed newborns. Conclusions : Although buprenorphine exposure during pregnancy does not seem to cause constant deficiencies in somatosensory or auditory processing, in some newborns the typical development of somatosensory networks may be – at least transiently – disrupted.